(untitled) - Cowan, M. Kelly (Boston, 2009)
Making Connections” Microbiology: A Systems Approach is a non-majors/allied health microbiology textbook that has quickly become known for its unique organization, engaging writing style, and instructional art program. Cowan’s “building blocks” approach establishes the big picture first and then gradually layers concepts onto this foundation. This logical structure helps students build knowledge and connect important concepts.
Keywords: Microbiology,Vi trùng học